Pain Assessment Discrepancies: A Cross‐Sectional Study Highlights the Amount of Underrated Pain. Issue 3 (20th September 2017) - van Ransbeeck, Andrea; Budilivski, Ana; Spahn, Donat R.; Macrea, Lucian; Giuliani, Francesca; Maurer, Konrad
Abstract: Background: Inadequately treated postoperative pain can lead to longer healing processes, longer hospital stays, and the development of chronic pain. In a 900‐bed university hospital in Switzerland, pain scores were assessed systematically. The study's primary aim was to define whether the routine pain assessment on the ward is accurate and reproducible. Subsequently the obtained data were used for a benchmark analysis to determine the hospital's performance in pain assessment quality compared with similar centers. Methods: During a 3‐month period, PAIN OUT questionnaires were used for patients' interviews. Patients were included randomly according to the daily surgical schedule. Pain scores were assessed routinely by nursing staff on the wards and compared to PAIN OUT data. The ascertained data were analyzed by descriptive statistics as well as the Wilcoxon test for nonparametric values using IBM SPSS. Results: 658 patients were included in the study. Comparing routine pain measurements with PAIN OUT results revealed that within the first 24 hours on the ward, pain scores were significantly lower than measured with PAIN OUT questionnaires. This difference increased with increasing pain scores. The quality of pain management of the hospital in which this study was performed ranged around the 50th percentile when compared to similar centers. Conclusion: The cross‐sectional data comparison of pain assessment by the ward staff and by interviews with the PAIN OUT questionnaire showed a large gap of underrated pain. The benchmark analysis with the method of PAIN OUT suggests a decent pain management among reference groups.